PENGARUH KEPEMILIKAN INSTITUSIONAL DAN TATA KELOLA PERUSAHAAN TERHADAP KINERJA PERUSAHAAN (Studi Empiris Pada Perusahaan Sektor Consumer Goods Yang Tercatat di PT. Bursa Efek Indonesia Tahun 2017-2019) - Alam Armansyah; Karlina Aprilia Kusumadewi (Diponegoro Journal of Accounting, 2022)
The goals of this research is to see how Corporate Governance affects the company business performance. Proxy Tobin’s Q is used in this study to determine how effective the firm is at using it’s assets to create profits and entice the investors to invest. The mechanism of good corporate governance is intended to decrease potential conflicts of agency and interest cost. As the result, the level of investor confidence and the company’s performance can both improve. The population in this study were Consumer Goods companies registered in Indonesia Stock Exchange for 3 consecutive years (2017-2019). Purposive sampling was employed to collect data for this investigation. The total number of research samples in this study were 85 study samples. A multiple linear regression analysis method is used in this investigation. The classical assumption test is performed first, before do the regression test. According to the findings if this study, institusional ownerships, independent comissioner, frequency meetings of commisioner and frequency meetings of Board of Directors have little impact on firm success. While the size of company’s Board of Directors has a significant positive effect on company performance, the independence of audit committees, on the other hand, has no significant impact on the company’s performance.